Ratih Mahardika PELATIHAN PEMBUATAN ALAT PERMAINAN EDUKATIF PENGENALAN MAKANAN BERGIZI UNTUK ORANG TUA ANAK USIA DINI - Ratih Mahardika (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2020)
The introduction of nutritious food is very important to be introduced to early childhood, of course introductioncan be done by parents, especially mothers by utilizing the time when playing. Teachers and parents have ahabit of getting play equipment or learning support tools to buy. But of course, these habits can fosterconsumptive nature and culture early on. It also triggers the weakening of creativity and innovation for children.Therefore there is a need for training to make or design educational toys based on simple craftsmanship withthe concept of introducing nutritious foods to children from an early age. This training will be aimed at mothersof early childhood. The method used in community service is to provide training to make an educational gametool about the introduction of nutritious foods from simple crafts.